O Programa Ler e Escrever e suas implicações no trabalho docente: o que avaliam os professores da rede de ensino estadual de São Carlos/SP? - Silva, Letícia Lais da (Universidade Federal de São Carlos, 2021)
The Reading and Writing Program, the object of this research, is an educational policy created by the Department of Education of the State of São Paulo focused on elementary school I and that proposes a set of mandatory actions that have been present in the state school system since 2007, including teacher training, monitoring, preparation and distribution of materials and guides for teachers, among others. From this context, this research aimed to analyze the Reading and Writing Program and its implementation in the state school system of São Carlos/SP, verifying its implications in the teaching work, based on the evaluation of teachers about this policy. As specific objectives, this study aimed to: understand the historical and political context of the Reading and Writing Program; analyze the structure and functioning of the Program, verifying, mainly in its materials, the relationship it maintains with teachers; identify whether teachers use reading and writing program materials in their daily activities, why and how; to investigate the contributions and limitations of the Reading and Writing Program in the development of teaching work, according to the teachers' analysis. To achieve the proposed objectives, bibliographic, documentary, and field research were used. Initially, a bibliographic and documentary analysis of the theme was made, with the intention of mapping the object of this research, in addition to studying its structure and functioning, as well as its history - whose theoretical field led to the study of the New Public Management, a new form of management of educational policies that have been incorporated in the State of São Paulo since the mid 1995s. Furthermore, this research also went through an empirical stage, using the on-line questionnaire as an instrument of data collection - sent to the teachers of the São Carlos state network, using the “Microsoft Office Forms” program. This stage obtained 24 collaborators, who agreed to respond to the survey. For data analysis and collection, this work used content categories, according to the perspective proposed by Kuenzer (1998). Categories were defined, in this sense: teachers' understanding of the material; daily teaching work and frequency/use of the Program materials; difficulties/limitations regarding the material and impact on teaching work; contributions for the use of materials to the teacher; teacher training. With this research, some results were reached, among them: teachers understand the materials of Reading and Write positively, but do not consider them sufficient for the reality lived in state schools, since they are out of the singularities existing in each context; they mention that there are difficulties in working with materials and that the limitations are to treat schools, teachers, and students in a standardized way; understand that the Program acts for the construction of a dependent teacher, who does not perceive himself capable and sufficient to create solutions to the reality itself; nevertheless, they also show that they often use the materials proposed by the Program, by making sense and meaning in each classroom, adapting them to the realities existing in schools. Thus, what is observed is that the Read and Write Program has contributed little to the quality of São Paulo's education, even less so, to the strengthening, care, and autonomy of teaching work. This is because, he has acted in the sense of trying to standardize contexts, practices, and contents, treating teachers from São Paulo as executors of a proposal produced by experts, but who do not measure and size what is lived in state schools.
The Program Read and Write and its implications in teaching work: what do teachers in the state school system of São Carlos/SP evaluate?
Keywords: Programa Ler e Escrever.; Trabalho docente.; Política Educacional Paulista.; Reading and Writing Program; Teaching work; Paulista Educational Policy; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL